Borrelia burgdorferi sensu lato inhibits CIITA transcription through pSTAT3 activation and enhanced SOCS1 and SOCS3 expression leading to limited IFN-γ production - Michelle A.E. Brouwer; Zara Karami; Samuel T. Keating; Hedwig Vrijmoeth; Heidi L.M. Lemmers; Helga Dijkstra; Frank L. van de Veerdonk; Mihaela Lupse; Hadewych J.M. ter Hofstede; Mihai G. Netea; Leo A.B. Joosten (Ticks and Tick-Borne Diseases)
Interferons (IFNs) are important signaling molecules in the human immune response against micro-organisms. Throughout initial Borrelia burgdorferi sensu lato (B. burgdorferi s.l.) infection in vitro, inadequate IFN-γ production results in the absence of a strong T-helper 1 cell response, potentially hampering the development of an effective antibody responses in Lyme borreliosis (LB) patients. The aim of this study is to help understand the immunomodulatory mechanisms why IFN-γ production is absent in the early onset of LB. Therefore, cytokine production and STAT activation signature, following exposure of human immune cells to B. burgdorferi s.l., was investigated in vivo and in vitro. While STAT3 phosphorylation was highly induced in T cells, B cells and NK-(T) cells, STAT1 expression and IL-12p70 production were not or only slightly increased upon B. burgdorferi s.l. exposure. In response to B. burgdorferi s.l., STAT2 phosphorylation and IFNα production remained stable. STAT2 activation only increased in NK-(T) cells. In contrast, STAT4 signaling was reduced in all B. burgdorferi s.l. exposed immune cells. Moreover, B. burgdorferi s.l. significantly increased suppressor of cytokine signaling (SOCS)1 and SOCS3 gene expression in LB patients. Absence of IFN-γ production and STAT4 activation, in combination with STAT3 phosphorylation and upregulated SOCS1 and SOCS3 gene expression, suggests the formation of a more tolerant and anti-inflammatory response to B. burgdorferi s.l., specifically in T- and B-cells. In primary human PBMCs and monocyte populations, B. burgdorferi s.l. also specifically interfered with CIITA isoforms normally expressed in antigen presenting dendritic cells. In contrast, it enhanced CIITA isoforms typically present in adaptive immune cell subsets. Restoring antigen presentation capacity of innate immune cells and early production of IFN-γ in LB patients may help re-establish immune functions during initial LB. These new insights will help to understand the immunomodulatory mechanisms of B. burgdorferi s.l. during the onset of LB.